The curvilinear responses of biomass accumulation and root morphology to a soil salt-nitrogen environment reflect the phytodesalination capability of the euhalophyte Suaeda salsa L. - Wang, Yanyan; Guo, Tongkai; Tian, Changyan; Zhao, Zhenyong; Zhang, Ke; Mai, Wenxuan (Frontiers in Plant Science, 2024)
In euhalophytes, the curvilinear responses of biomass accumulation and root morphology in response to soil salinity have been recognized, but these perceptions are still confined to the descriptions of intertreatment population changes, and lack the details on biomass allocation among the organs at the individual level. Under the sufficient nitrogen supply, it is of great significance to investigate the law of biomass allocation, root morphological traits and its salt absorption capacity of euhalophytes, for evaluating their biological desalination in saline soil dominated by sodium chloride. Suaeda salsa L. were grown in the root boxes across a range of soil salt levels, and their growth and development significantly affected by soil soluble salts. Based on this study, the law of biomass allocation was summarized and described as follows: The increased soil soluble salts led to a significant increase in leaf mass ratio and decrease in stem mass ratio, and a slight increase in root mass ratio among treatments. For individuals at each treatment, leaf mass ratio > stem mass ratio > root mass ratio, except in the control treatment at the flower bud and fruit stages. Biomass responses of control treatment indicated that salt was not rigorously required for S. salsa in the presence of adequate nitrogen supply, as verified by the correlation between biomass, nitrogen and soil soluble salt. Salt could significantly inhibit the growth of S. salsa (P<0.01), while nitrogen could significantly promote its growth (P<0.01). Root morphology in response to soil soluble salts showed salt acquisition by the root was the highest at 0.70% salt level, corresponding to light saline soil. Consequently, we draw the conclusion that phytodesalination of S. salsa was the optimal in the light saline soil, followed by moderate saline soil.